A Necessary Hegemonic Relationship? American Accrediting Organizations and their Link with Higher Education in Latin America - Moreno Rosano, María Patricia; Gómez Bonilla, Rosendo Edgar; Rodríguez Ortiz, Guillermo Alberto (Araucaria, 2017)
The influence of the United States in its diverse manifestations has a long history in Latin America. While research and academic studies over the course of recent decades have highlighted the strong influence of the United States in the international economic and political arenas, few have alluded to its hegemonic but subtle influence on higher education in the region. The practices of evaluating and accrediting institutions and educational programs around the world as a means for society to hold them to account and ensure compliance with certain quality parameters have predominated throughout the last three decades. The foregoing would give reason to conclude that the United States is the nation with the most experience in the evaluation and accreditation of educational institutions and programs. Recently, this hegemony has taken another form, with the direct accreditation, by American accreditors, of Latin American higher education institutions and programs.